Measuring System Performance or Just Counting: A conceptual analysis - Dinesh Arya (Asia Pacific Journal of Health Management)
Purpose – The paper explores the concept of performance measurement and identifies that when measurement information does not inform about the performance of the system, it is not used and the effort becomes wasteful. Strategies to make performance measurement and reporting more meaningful are identified.